2005
DOI: 10.1083/jcb.200504061
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac neural crest cells contribute to the dormant multipotent stem cell in the mammalian heart

Abstract: Arodent cardiac side population cell fraction formed clonal spheroids in serum-free medium, which expressed nestin, Musashi-1, and multi-drug resistance transporter gene 1, markers of undifferentiated neural precursor cells. These markers were lost following differentiation, and were replaced by the expression of neuron-, glial-, smooth muscle cell–, or cardiomyocyte-specific proteins. Cardiosphere-derived cells transplanted into chick embryos migrated to the truncus arteriosus and cardiac outflow tract and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
268
3
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(287 citation statements)
references
References 52 publications
10
268
3
5
Order By: Relevance
“…This discrepancy in expression levels suggests that nestin + and GATA-4 + cells could be derived from other cell lineages, including c-Kit -cells. In this respect, Tomita et al (2005) showed that neural crest-derived cells migrate and lay in a dormant, undifferentiated state in the heart expressing nestin and GATA-4 or can differentiate into cardiomyocytes or in vitro-derived cardiospheres.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy in expression levels suggests that nestin + and GATA-4 + cells could be derived from other cell lineages, including c-Kit -cells. In this respect, Tomita et al (2005) showed that neural crest-derived cells migrate and lay in a dormant, undifferentiated state in the heart expressing nestin and GATA-4 or can differentiate into cardiomyocytes or in vitro-derived cardiospheres.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, endogenous Gata-4 has not been detected (Pilon et al, 2008). In other reports, Gata-4 expression has been described in some neural crest-derived cardiac progenitors (Tomita et al, 2005) and in primitive neural stem cell spheres (Hitoshi et al, 2004).…”
mentioning
confidence: 97%
“…When transplanted into chick neural tube, cardiosphere cells behaved as neural crest and migrated into the outflow tract, DRGs and spinal nerve and followed the lateral migration pathway. Together, this evidence suggests that a population of neural crest-derived stem cells remains in the heart and has capacity to differentiate (Tomita et al, 2005).…”
Section: Cardiac Ncscsmentioning
confidence: 83%
“…A neural crest-derived stem cell population has also been identified within the adult mice cardiac side population (SP; Tomita et al, 2005). SP cells are dormant, multipotent cells that are found in a variety of tissues and can be identified by their differential ability to efflux the Hoechst 33342 dye.…”
Section: Cardiac Ncscsmentioning
confidence: 99%